2020
DOI: 10.18231/2456-9542.2018.0028
|View full text |Cite
|
Sign up to set email alerts
|

Extemporaneous compounding: Cautions, controversies and convenience

Abstract: Pharmacists are only knowledgeable and skilled healthcare professionals dedicated to compounding and preparing medications to meet the unique needs of patients. The safe and effective extemporaneous compounding of prescription products for patients require in special care is fundamental to the pharmacy profession. But there are much to do for secundum artem. It is not at all economical for a pharmaceutical company to marketize a product in 10 different probable doses or in 5 different dosage forms to meet the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Usually, to progressively reduce the dose of drug, prescribers recommend the tablets to be cut in half to obtain 5.0 mg of drug. However, it has previously been demonstrated that such a practice may generates a variability ranged from 50% to 150% of the targeted dose [Mohiuddin, 2019].…”
Section: Determination Of the Dimension Of The Printletsmentioning
confidence: 99%
See 2 more Smart Citations
“…Usually, to progressively reduce the dose of drug, prescribers recommend the tablets to be cut in half to obtain 5.0 mg of drug. However, it has previously been demonstrated that such a practice may generates a variability ranged from 50% to 150% of the targeted dose [Mohiuddin, 2019].…”
Section: Determination Of the Dimension Of The Printletsmentioning
confidence: 99%
“…However, it has been demonstrated that such tablets cannot be cut with sufficient accuracy of dose, even when a commercially tablets cutter is used. Indeed, research suggest that the variability may range from 50% to 150% of the targeted dose [Mohiuddin, 2019]. Faced with the therapeutic limitations inherent to marketed products, magistral preparations offer medical and legal alternatives to mass treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapies available for the treatment of cancers include chemotherapeutic agents, biologics, molecular-targeted therapy, radiotherapy, surgery, and interventional oncology (Ramos et al, 2021;Sag et al, 2016). In the pharmaceutical area, the manipulation of injectable drugs is a complex activity, since they are not commercially available, making it possible to prepare them in a personalized way to solve the specific needs of the patient: individualization of the dose, addition of components to the formulation, choice of the type of diluent volume suitable for the clinical condition of the patient and adequacy of the formulation to the route of administration ("ASHP Guidelines on Compounding Sterile Preparations", 2014; Mohiuddin, 2020;Pergolizzi Jr et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, the difficulty is based on the fact that they can impair and also improve the acquisition and retention of learned responses in the organism in which it was administered (McGaugh 1973). These drugs are not commercially available, with the possibility of personalizing the preparation to meet the specific needs of the patient: individualization of the dose, adaptation of the formulation to the route of administration, adding components to the formulation and choosing the type of diluent volume suitable for the patient's clinical condition ("ASHP Guidelines on Compounding Sterile Preparations", 2014; Mohiuddin, 2020;Pergolizzi Jr et al, 2013). Regarding the handling of antineoplastic drugs, their correct handling is essential to ensure success in the treatment of cancer patients, as any error in dosage can lead to irreversible damage (ABRALE, 2020).…”
Section: Introductionmentioning
confidence: 99%